Laparoscopic bilateral salpingo-oophorectomy for recurrent ovarian endometriotic cysts in a woman taking adjuvant tamoxifen for breast cancer: A case report - Hajime Takeuchi; Koki Yagi; Naho Tokunaga; Naoki Abe; Mariko Matsuno; Sachino Kira; Sotaro Hayashi; Lifa Lee; Yoko To; Satoshi Nishiyama; Maki Goto; Hiroshi Tsujioka (Elsevier, 2024)
The case report describes the management of endometriotic cysts in a woman taking adjuvant tamoxifen. A diagnosis of endometriosis was made at the age of 38, and the condition was initially managed with a low-dose estrogen-progestogen combination; the patient then switched to dienogest at the age of 45. Following a diagnosis of breast cancer at the age of 46, dienogest was stopped and adjuvant tamoxifen treatment started. After 4 months the patient was diagnosed with bilateral ovarian cysts and underwent laparoscopic bilateral salpingo-oophorectomy. Endometriosis was diagnosed in both ovaries on histopathological examination. This case report describes progression of endometriosis in a tamoxifen user.